Innovative Orbital Periosteum Suturing Technique for Endoscopic Medial Orbital Wall Reconstruction - Takeda, Teppei; Hardison, Scott; Omura, Kazuhiro; Ishii, Yudo; Mori, Ryosuke; Kimple, Adam J.; Senior, Brent A.; Otori, Nobuyoshi; Klatt-Cromwell, Christine; Thorp, Brian D. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Advances in endoscopic orbital surgery have sparked discussion regarding reconstructive procedures for medial orbital wall defects following tumor removal. This study describes an innovative orbital periosteal suturing technique that addresses the functional and aesthetic concerns created by orbital surgery.Comprehensive clinical evaluation of a novel orbital periosteal suturing technique for endoscopic medial orbital wall reconstruction.A retrospective chart review identified five patients who underwent endoscopic transnasal resection and subsequent orbital periosteal suturing for reconstruction. The surgical approach involved a binostril transseptal technique to create a broad surgical corridor. The postoperative follow-up was 13.4 ± 1.8 months.In the five patients, the mean age was 47.6 ± 13.0 years and the lesions were predominantly distributed on the left side (60%). Reconstruction time with the orbital periosteal suture procedure averaged 47.2 ± 6.6 minutes, employing four to five stitches. No patients experienced short-term complications such as visual acuity defect, new or exacerbated diplopia, or cranial nerve palsy within 2 weeks, and no long-term complications such as enophthalmos or prolonged diplopia were observed.Orbital periosteal suturing is an effective and resource-efficient technique for endoscopic reconstruction of the medial orbital wall. Surgeons may consider this method among the available options for orbital reconstruction, representing a novel advancement in the field.
Keywords: orbital periosteal suturing; endoscopic reconstruction; medial orbital wall reconstruction; orbital tumor resection; surgical technique; skull base surgery; orbital surgery